1992
DOI: 10.1046/j.1469-0705.1992.02060424.x
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal color Doppler study of middle cerebral artery blood flow in early normal and abnormal pregnancy

Abstract: Transvaginal color and pulsed Doppler sonography was performed on 106 singleton pregnant women; 75 had clinically normal pregnancies, and the remaining 31 patients had complicated pregnancies with vaginal bleeding. The gestational ages ranged from the 7th to 18th menstrual weeks. The aim of the study was to establish the earliest gestational age at which intracranial blood flow could be detected, in particular in the middle cerebral artery. The intracranial circulation becomes visible at the 8th week of gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…Few studies have addressed this issue. Kurjak et al [ 15] found that Doppler studies of the middle cerebral artery in early pregnancy were unlikely to be of value in identifying fetal hemodynamic disorders in the early stages of spontaneous abortion. More recently,…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have addressed this issue. Kurjak et al [ 15] found that Doppler studies of the middle cerebral artery in early pregnancy were unlikely to be of value in identifying fetal hemodynamic disorders in the early stages of spontaneous abortion. More recently,…”
Section: Discussionmentioning
confidence: 99%
“…The middle cerebral artery, as the terminal branch of the internal carotid artery, has been visualized at the base of the fetal brain [12] from the 8th to 11th gestational week as well as at the level of the heart-shaped cerebral peduncles at its lateral-anteral borders, running anterolaterally towards the lateral edge o f the orbit (from the 11th to 16th gestational week). When blood flow was obtained, pulsed Doppler sample volume was focused on it and the resistance index (RI) was calculated in the uteroplacental arteries, while in fetal vessels the pulsatility index (PI) was measured.…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Kurjak et al [30] using transvaginal ultrasound, the visualization rate of pulsation on the base of the skull increased from 50% at the 8th gestational week to 83% at the 10th week. From the 11th week onwards it became a constant finding.…”
Section: Cerebral Arterial Doppler Waveforms In Normal Fetusesmentioning
confidence: 98%